Investigating the determinants of partnership and community development programs: Indonesia perspectives - Indira Januarti; Faisal Faisal; Resi Juliati Situmorang (Cogent Business & Management, 2019)
The purpose of this study is to provide evidence on the relationship between firm visibility and partnership and community development programs. The Partnership and Community Development (PCD) program was designed by government to enhance the capabilities of small businesses and improve social conditions in Indonesia. Through the PCD program, companies can optimize and create a synergy between their activities and stakeholders to achieve community welfare. A sample was selected from the Ministry of State-Owned Enterprises' website in 2017. The annual and sustainability reports of all State-owned Enteprises were examined to measure the performance of PCD programs. The financial data were sourced from the Bloomberg database. Firm visibility was measured by profitability, firm size and capital intensity. This study provides evidence on the relationship between profitability, firm size, capital intensity and the level of engagement in the PCD program. This finding suggests that the visibility of SOEs is a significant driving force for participation in social responsibility activities through the PCD program. This study augments accounting and business literature by exploring the role of government as the primary stakeholder in encouraging the uptake of PCD. This finding suggests that the stakeholder pressure on SOEs in improving PCD programs seems can be explained by stakeholder theory This study is one of a few studies to investigate the impact of firm visibility on partnership and community development programs in a developing country.
Keywords: 650; Sustainability; partnership; community development; stakeholder; state-owned enterprises; Indonesia